Proteôma do músculo (Pectoralis major) e do sistema reprodutor de codornas europeias (Coturnix coturnix coturnix) alimentadas com anacardato de cálcio e ácido cítrico - Vilarinho, Nhaira Maia (2023)
The present thesis had two objectives: Study 1) describe the proteome of the Pectoralis Major muscle, testis, epididymis and accessory gland subjected to different levels containing anacardic calcium and citric acid, as well as, histological analysis of the testis of European quails (Coturnix coturnix coturnix ) using mass spectrometry. Study 2) describe the proteome of the testicular tissue of European quails (Coturnix coturnix coturnix). For this, 63 European quails, aged 21 weeks, were distributed in a completely randomized design of nine treatments and seven replications. The treatments consisted of: T1- food without the addition of calcium anacardate (ANC); T2- food with addition of 0.25% ANC; T3- food with addition of 0.25% ANC and 0.25% citric acid (CA); T4- food with addition of 0.50% ANC; T5- food with addition of 0.50% ANC and 0.25% AC; T6- food with addition of 0.50% ANC and 0.50% AC; T7- food with addition of 0.75% ANC; T8- food with addition of 0.75% ANC and 0.25% AC; T9- ration with addition of 0.75% ANC and 0.50% AC. After slaughtering the animals, they were weighed and measurements were taken, subsequently lyophilized, proceeding with protein extraction, followed by tryptic digestion, 1 D electrophoresis and analysis of the peptides by LC-MS/MS. We identified 64 proteins in the muscle gel, 44 testis proteins, 60 epididymis proteins and 66 accessory gland proteins. Treatments containing 0.50% calcium anacardate and 0.25% citric acid showed greater intensity in the expression of proteins in testicular tissue, with the following proteins: Glyceraldehyde-3-phosphate dehydrogenase, Tudor domain-containing protein 7, Myosin -binding protein C, fast-type, Ubiquitin-40S ribosomal protein S27a, Heat shock protein HSP 90-alpha, Superoxide dismutase [Cu-Zn], Ubiquitin-conjugating enzyme E2 variant 2, Creatine kinase B-type, Peroxiredoxin-1, among others. The present work suggests that the inclusion of acids in the quail diet should include 0.25% to 0.50% of calcium anacardate associated with 0.25% of citric acid. For study 2, after the slaughter of the animals, the tissues from the control treatment were collected, lyophilized, proceeding with protein extraction, followed by tryptic digestion, desalination and analysis of the peptides by LC-MS/MS. In this category, 2,784 proteins were identified, in which heat shock proteins, tubulin, creatine kinase, actin, ATP synthase, transitional endoplasmic reticulum ATPAse, pyruvate, endoplasmin and glyceraldehyde-3-phosphate dehydrogenase were confirmed as the most abundant. The data was analyzed with the aid of bioinformatics tools according to miRNAs through gene selection, gene ontology, protein grouping, protein-protein interaction and metabolic pathways. The upload of 2784 Uniprot access codes through the DAVID platform corresponded to 1,563 genes, which were mainly related to ATP binding, structural constituent of the ribosome, translation, among others. The work provides the first characterization of the proteome of European quail testicular tissue.